2017
DOI: 10.1007/s11886-017-0902-6
|View full text |Cite
|
Sign up to set email alerts
|

Intracardiac Echocardiography for Structural Heart and Electrophysiological Interventions

Abstract: Both transthoracic (TTE) and transesophageal echocardiography have limitations. ICE provides the advantage of imaging from within the heart, providing shorter image distances and higher resolution. ICE may be performed without sedation and avoids esophageal intubation as with transesophageal echocardiography (TEE). Limitations of ICE include the need for additional venous access with possibility of vascular complications, potentially higher costs, and a learning curve for new operators. Data supports the use o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 72 publications
0
37
0
1
Order By: Relevance
“…Finally, intracardiac echocardiography (ICE) is an alternative imaging method of the LAA, usually indicated when TOE is contraindicated or not obtainable. ICE is performed with an 8–10 Fr catheter introduced through femoral venous access and advanced in right heart chambers under fluoroscopic guidance [38]. In the absence of interatrial transseptal crossing, the LAA can be displayed indirectly through the right ventricle outflow tract and the pulmonary artery, considering their close anatomical relationship [39].…”
Section: The Role Of Echocardiography Before Cardioversionmentioning
confidence: 99%
“…Finally, intracardiac echocardiography (ICE) is an alternative imaging method of the LAA, usually indicated when TOE is contraindicated or not obtainable. ICE is performed with an 8–10 Fr catheter introduced through femoral venous access and advanced in right heart chambers under fluoroscopic guidance [38]. In the absence of interatrial transseptal crossing, the LAA can be displayed indirectly through the right ventricle outflow tract and the pulmonary artery, considering their close anatomical relationship [39].…”
Section: The Role Of Echocardiography Before Cardioversionmentioning
confidence: 99%
“…With the widespread use of the Amplatzer occluder and the rapid development of interventional techniques, traditional radiographically guided percutaneous interventional ASD closure has been proven to be a safe and effective method [ 1 , 2 ]. Some scholars [ 6 ] used intracardiac echocardiography to guide percutaneous transluminal atrial septal occlusion in the early years, but the cost of the corresponding catheter is not suitable for China's current national conditions. In recent years, to avoid radiation damage to patients and doctors, the use of echocardiography to gradually and completely replace radiation for interventional therapy has become an important method for improving traditional percutaneous interventional techniques [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…After the position of the delivery sheath is determined, the relationship between the released device and surrounding structures can be effectively observed in combination with the four-chamber views, including the mitral valve and pulmonary veins, which ensures the safety of the device release and avoids the occurrence of complications. Furthermore, we avoid the use of harmful X-rays and expensive intracardiac ultrasound [ 6 ] to complete the entire occlusion procedure quickly and efficiently by minimizing the number of views conversions while ensuring the quality of the imaging, optimizing the process, and ensuring the quality of the procedures.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, in our patient we used the ViewFlex Xtra catheter that has a large curvature radius with different steering angles from 0 to 120 degrees with a simple onehand torsional control. The ViewMate Zonare console operates in different modes for high resolution 2D imaging of cardiac structures with intuitive on-screen menus for color, pulsed and continuous Doppler [9]. As the above mentioned authors did, we identified the anatomical tricuspid annulus with the help of ICE and ablated the accessory pathway using radiofrequency applications.…”
Section: Discussionmentioning
confidence: 99%